Consumers’ Satisfaction towards Current Brand of Yasoda Foods Products in Kathmandu Valley - Poudel, Om Narayan (Nepalese Journal of Economics, 2025)
This study examines the consumers’ satisfaction towards current brand of Yasoda foods products in Kathmandu Valley. Consumer satisfaction is the dependent variable. The selected independent variables are price, taste, quality, packaging, quantity and availability. The primary sources of data is used to assess the opinions of respondents regarding price, taste, quality, packaging, quantity and availability. The study is based on the primary data of 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the consumers’ satisfaction towards current brand of Yasoda foods products in Kathmandu Valley. The study showed a positive impact of price on consumer satisfaction. It indicates that affordable price provided by Yasoda foods to consumers’ leads to increase in consumer satisfaction. Similarly, the study showed a positive impact of taste on consumer satisfaction. It indicates crunchiness and spicy in taste of current brand leads to increase in consumer satisfaction. Likewise, the study showed a positive impact of quality on consumer satisfaction. It indicates that food quality of current brand leads to increase in consumer satisfaction. In addition, the study showed a positive impact of packaging on consumer satisfaction. It indicates that attractive packaging leads to increase in consumer satisfaction. Further, the study showed a positive impact of quantity on consumer satisfaction. It indicates that huge quantity of product leads to increase in consumer satisfaction. Moreover, the study showed a positive impact of availability on consumer satisfaction. It indicates that availability of current brand products lead to increase in consumer satisfaction.